2007
DOI: 10.1007/s10552-007-9021-9
|View full text |Cite
|
Sign up to set email alerts
|

Dietary lipids and endometrial cancer: the current epidemiologic evidence

Abstract: Background: Because dietary fat has been postulated to affect obesity and estrogen levels, two important risk factors for endometrial cancer, its association with this disease has received some attention. We summarize here the current evidence for several dietary lipids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
2
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 47 publications
2
43
2
1
Order By: Relevance
“…The literature with respect to calcium and endometrial carcinogenesis is limited. In a rodent model, calcium reduces fat-induced cell proliferation by maintaining intracellular calcium concentrations (Jacobson et al, 1989) and greater fat intakes has been related to endometrial cancer risk (Bandera et al, 2007b). Calcium has been inversely associated with risk of breast cancer, another hormone-dependent cancer (Mccullough et al, 2005;Shin et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The literature with respect to calcium and endometrial carcinogenesis is limited. In a rodent model, calcium reduces fat-induced cell proliferation by maintaining intracellular calcium concentrations (Jacobson et al, 1989) and greater fat intakes has been related to endometrial cancer risk (Bandera et al, 2007b). Calcium has been inversely associated with risk of breast cancer, another hormone-dependent cancer (Mccullough et al, 2005;Shin et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In the 2007 WCRF report, only 1 cohort study was cited [279] (LOE IIa) which examined the association between SFA intake and endometrial cancer. However, no risk association was found [257] (LOE IIa).…”
Section: Quantity and Quality Of Dietary Fat And Fatty Acid Intakementioning
confidence: 99%
“…The SLR for the WCRF report cited 1 cohort study, which showed no risk association [279] (LOE IIa). In the updated version of the WCRF report [261] (LOE IIa), MUFA were not covered for this carcinoma.…”
Section: Quantity and Quality Of Dietary Fat And Fatty Acid Intakementioning
confidence: 99%
See 1 more Smart Citation
“…The association between dietary cholesterol and EC has been assessed in nine previous case-control studies (20,(22)(23)(24)(25)28,31,32,34) with mixed results: three found statistically significant increased risks (20,24,32) , but the remaining six found non-significant reduced risks (23,25) , no association (34) or non-significant increased risks (22,28,31) . A pooled analysis of six of these studies reported a non-statistically significant increased risk of 35-39 % with higher cholesterol intake (29) . Studies of serum cholesterol have shown similar mixed results (35)(36)(37)(38)(39)(40)(41) .…”
Section: Discussionmentioning
confidence: 99%